Penyelenggara Jaminan Sosisal Ketenagakerjaan Terhadap Sektor Jasa Konstruksi Di Provinsi Kepulauan Riau - Rina Shahriyani Shahrullah; Wagiman Wagiman; Surya Rizal (Fakultas Hukum, Universitas Internasional Batam, 2014)
The law theories used by the researcher were the progressive law theory and law affectivity law theory with empirical research method to analyze how legislations were implemented in. The results showed that not all of the constructions projects at Riau Islands Province had been registered at Tanjungpinang Labor Social Security Agency, so that not all of the workers got the normative rights and legal protection on the social risks such as sickness, working accident, disability, and death. In Undang-Undang RI Number 40 year 2004 about National Social Security System, Ministry of Labors and Transmigration Decree Number KEP-196/MEN/1999, and Riau Islands Governor Legislation Number 18/XI/2005 about Constructions Service Sector Labors Social Security Programs had obligated the constructions service employers to register their labors to Labor BPJS. The implementation of labor social security programs for constructions workers was not optimal because of some factors, starting from the governments who were not firm and the lack of control, the employers who were lack of the awareness about the duty and still thinking that being BPJS member was a burden, the labors who did not care about their rights because they were lack of education, and the agency who did not maximize the socialization. From the progressive law point of view starting from the basic assumption that law was for humanity not the other way around, a law problem raised so that the legislations should be fixed including the behaviors of the employers/contractors, the government, and also the Social Security Agency itself. While if it was related to the affectivity theory, the constructions service sector labors protection implementation would not be well implemented without the good enforcement and.